REACHING OUT TO THOSE WHO WERE ONCE LOST: REFLECTIVE PERSONAL DAKWAH BY A RELIGIOUS COUNSELOR WITHIN A CIRCLE OF FORMER TERRORISM CONVICTS IN POHUWATO - Wisno Pakaya; Arfan Nusi; Dian Adi Perdana (Universitas Islam Negeri Mataram, 2026)
This research aims to examine the process of reflective personal dakwah in efforts toward deradicalization and the social reintegration of former terrorism convicts (ex-napiter) in Pohuwato Regency, Gorontalo Province, as carried out by a religious counselor (hereinafter referred to by the pseudonym Ustadz Wisno) toward seven ex-napiter. This approach emphasizes empathetic communication, spiritual accompaniment, and a humanizing space for reflection. The method used is reflective-participatory ethnography, in which the researcher acts as an insider-adjacent observer who follows, documents, and reflects upon the dakwah process carried out by the religious counselor, rather than as a direct practitioner of that dakwah. Data were obtained through in-depth interviews, participatory observation, and field notes over the period 2023–2025. The findings show that reflective personal dakwah contributed to the building of trust, verbal statements of ideological transformation, and the strengthening of social participation among the ex-napiter within the framework of the Unitary State of the Republic of Indonesia (NKRI). This research explicitly distinguishes between disengagement (changes in behavior and social involvement, which are observed more strongly in this study) and deradicalization (profound changes in ideological attitudes and beliefs, the verbal expressions of which need to be read with caution given the methodological limitations in verifying their depth). In conclusion, reflective personal dakwah is a promising humanity-based approach in supporting disengagement and post-sentence social reintegration, with certain elements that have the potential to be replicated by other religious counselors, although the sustainability and depth of ideological transformation require further, more systematic study.